The Nexus between Economic Liberalisation and Economic Growth:Empirical Evidence from ASEAN,China, and India - Selvarajan, Sonia Kumari; Rossazana, Ab. Rahim (Universiti Malaysia Kelantan, 2015)
The main objective of this paper is to examine the impact of economic liberalisation on economic growth. This paper also explores the relationship between trade and financial liberalisation. The analysis focuses on all ASEAN countries as well as China and India. Using the Generalised Method of Moment (GMM) dynamic panel data analysis, this paper finds that economic liberalisation is significantly related to economic growth in ASEAN6 and CLMV. For ASEAN, China, and India as a whole, trade openness has no significant impact on economic growth. However, a strong financial growth nexus exists. In ASEAN6 and CLMV, the results indicate that economic liberalisation leads to economic growth.